The Influence Of Price, Location And Service Quality On Passenger Satisfaction At PT Titisan Sang Pangeran (TISPA) - Yesie Aryanty; Aslamia Rosa; Zakaria Wahab; Marlina Widiyanti (Al-Makki Publisher, 2024)
This study was conducted to determine the effect of price, location, and service quality on passenger satisfaction at PT Titisan Sang Pangeran (Tispa). The population in this study were passengers at PT Titisan Sang Pangeran who used services during the 2023 period. The sample taken in this study was 300 passengers at PT Titisan Sang Pangeran who used services during the 2023 period using the purposive sampling method. The results of multiple linear regression analysis show that price, location, and service quality have a positive and significant effect on passenger satisfaction. Price, it is hoped that PT Titisan Sang Pangeran can evaluate pricing with the quality of service, facilities, and prices set by similar competitors. Location, it is expected to add a name sign from the street corner. Regarding service quality, it is hoped that an evaluation will be carried out regarding what are the obstacles in-service officers in responding to consumers both by telephone and WhatsApp. the purpose of this study is to determine, measure, and evaluate aspects of the quality of service provided to passengers.